Mistranslation Drives Alterations in Protein Levels and the Effects of a Synonymous Variant at the Fibroblast Growth Factor 21 Locus. Issue 11 (1st May 2021) - Bayoumi, Ali; Elsayed, Asmaa; Han, Shuanglin; Petta, Salvatore; Adams, Leon A.; Aller, Rocio; Khan, Anis; García‐Monzón, Carmelo; Arias‐Loste, María Teresa; Miele, Luca; Latchoumanin, Olivier; Alenizi, Shafi; et al.
Abstract: Fibroblast growth factor 21 (FGF21) is a liver‐derived hormone with pleiotropic beneficial effects on metabolism. Paradoxically, FGF21 levels are elevated in metabolic diseases. Interventions that restore metabolic homeostasis reduce FGF21. Whether abnormalities in FGF21 secretion or resistance in peripheral tissues is the initiating factor in altering FGF21 levels and function in humans is unknown. A genetic approach is used to help resolve this paradox. The authors demonstrate that the primary event in dysmetabolic phenotypes is the elevation of FGF21 secretion. The latter is regulated by translational reprogramming in a genotype‐ and context‐dependent manner. To relate the findings to tissues outcomes, the minor (A) allele of rs838133 is shown to be associated with increased hepatic inflammation in patients with metabolic associated fatty liver disease. The results here highlight a dominant role for translation of the FGF21 protein to explain variations in blood levels that is at least partially inherited. These results provide a framework for translational reprogramming of FGF21 to treat metabolic diseases. Abstract : Paradoxically, fibroblast growth factor 21 (FGF21) levels—a hormone with beneficial effects on metabolism—are elevated in metabolic diseases. It is shown that the primary event is elevation of FGF21 secretion via mistranslation in a genotype and context dependent manner. These results provide a framework for translational reprogramming of FGF21 to treat metabolic diseases.